Analysis Of Spaylater Practices Based On Fintech From An Islamic Economic Perspective - Alfina Lailatul Fitriyah; Ainur Rona Salsabila; Zahwa Aulia Rahma; Abdimalik Mohammed; Ana Tony Roby Chandra Yudha (Asosiasi Dosen Muda Indonesia, 2025)
The rapid development of financial technology has given rise to various financial product innovations, one of which is the Buy Now, Pay Later (BNPL) service, such as SPayLater, which is increasingly popular among Indonesians. This phenomenon has created an urgent need to analyze the compatibility of this practice with Islamic economic principles. The purpose of this study is to describe and analyze the operational mechanisms of SPayLater from an Islamic economic perspective. This study uses a qualitative method with a documentary study approach. Data was collected by identifying and examining public information listed on the Shopee application regarding SPayLater products, which includes terms and conditions, cost structures, and penalty policies. The collected data was then analyzed using qualitative content analysis techniques to describe the mechanisms of the SPayLater practice organized by PT Commerce Finance and evaluate them based on Sharia law standards. The results of the study indicate that the SPayLater practice contains several elements that fundamentally contradict the principles of Islamic muamalah. Three main aspects were found that make this service haram: first, the imposition of interest on installments, which is clearly categorized as riba an-nasi'ah; second, late fees, which are also a form of riba because they are a source of income for lenders; and third, percentage-based administrative fees that contain elements of gharar (uncertainty), thus not meeting the requirement of clarity of wages (ujrah).